Magnesium Application Promotes Rubisco Activation and Contributes to High-Temperature Stress Alleviation in Wheat During the Grain Filling - Shao, Yuhang; Li, Shiyu; Gao, Lijun; Sun, Chuanjiao; Hu, Jinling; Ullah, Attiq; Gao, Jingwen; Li, Xinxin; Liu, Sixi; Jiang, Dong; Cao, Weixing; Tian, Zhongwei; et al. (Frontiers in Plant Science, 2021)
Inhibited photosynthesis caused by post-anthesis high-temperature stress (HTS) leads to decreased wheat grain yield. Magnesium (Mg) plays critical roles in photosynthesis; however, its function under HTS during wheat grain filling remains poorly understood. Therefore, in this study, we investigated the effects of Mg on the impact of HTS on photosynthesis during wheat grain filling by conducting pot experiments in controlled-climate chambers. Plants were subjected to a day/night temperature cycle of 32°C/22°C for 5 days during post-anthesis; the control temperature was set at 26°C/16°C. Mg was applied at the booting stage, with untreated plants used as a control. HTS reduced the yield and net photosynthetic rate (Pn) of wheat plants. The maximum carboxylation rate (VCmax), which is limited by Rubisco, decreased earlier than the light-saturated potential electron transport rate. This decrease in VCmax was caused by decreased Rubisco activation under HTS. Mg application reduced yield loss by stabilizing Pn. Rubisco activation was enhanced by increasing Rubisco activase activity following Mg application, thereby stabilizing Pn. We conclude that Mg maintains Rubisco activation, thereby helping to stabilize Pn under HTS.